2000
DOI: 10.1128/jb.182.15.4257-4263.2000
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Major Heat Shock Genes of Helicobacter pylori

Abstract: The transcriptional organization and heat inducibility of the major heat shock genes hrcA, dnaK, dnaJ, groEL, and htpG were analyzed on the transcriptional level in Helicobacter pylori strain 69A. The strongly heat-induced dnaK operon was found to be tricistronic, consisting of the genes hrcA, grpE, and dnaK. The dnaJ gene specified one monocistronic mRNA which was also heat inducible. The genes groES and groEL were transcribed as one strongly heat-inducible bicistronic mRNA which exhibited exactly the same in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 45 publications
1
32
1
1
Order By: Relevance
“…1. P gro transcribes one bicistronic mRNA encoding the chaperonin machinery GroESL; P hrc transcribes a tricistronic mRNA encoding the putative repressor HrcA, the chaperone DnaK, and its cochaperone GrpE (8,17); and P cbp is likely to transcribe a tricistronic mRNA encoding the DnaJ homologue CbpA, the HspR repressor, and a putative DNA helicase (17). To investigate the transcriptional response of these promoters to a sudden temperature increase, total RNA was isolated from H. pylori strain G27 grown at 37°C and at different time points after upshift of the culture to 42°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1. P gro transcribes one bicistronic mRNA encoding the chaperonin machinery GroESL; P hrc transcribes a tricistronic mRNA encoding the putative repressor HrcA, the chaperone DnaK, and its cochaperone GrpE (8,17); and P cbp is likely to transcribe a tricistronic mRNA encoding the DnaJ homologue CbpA, the HspR repressor, and a putative DNA helicase (17). To investigate the transcriptional response of these promoters to a sudden temperature increase, total RNA was isolated from H. pylori strain G27 grown at 37°C and at different time points after upshift of the culture to 42°C.…”
Section: Resultsmentioning
confidence: 99%
“…The control of transcription by HspR depends on the binding of this protein to large operators mapping to different positions surrounding the promoters (17). In addition to this regulation, the possibility that another transcriptional repressor, a homolog of the B. subtilis HrcA protein (16) encoded by the hrcA-grpE-dnaK locus, might also be involved in controlling stress response has been postulated (8,17). Evidences that chaperone gene transcription in this system responds to an increase in salinity and temperature elevation to 42°C, but not to 45°C, have been recently reported (8,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies indicated that while transcription of the groESL and cbpA-hspR-orf operons was strongly inducible by treatment with 300 mM NaCl, no induction was observed when cultures were incubated at 45°C (31). Subsequently, Homouth and coworkers (15) showed that transcription of these operons is strongly inducible by a mild heat shock at 42°C, suggesting that HspR can indeed mediate the transcriptional response to a sudden temperature increase, characterized by fast and strong induction of transcription and a subsequent shutoff phase, whose onset is determined largely by the stability of the respective mRNAs (29). Until recently, the study of HrcAdependent regulation was hampered by difficulties in purifying a recombinant protein to map the HrcA binding sites on the promoters (25,31).…”
mentioning
confidence: 99%
“…Interestingly, the molecular chaperone genes dnaJK, the heat shock protein gene grpE, and the heat shock response transcriptional regulator gene hrcA, and the chaperone genes groESL, the ATP-dependent clp protease genes clpEPC, and the transcriptional regulator gene ctsR, show higher FPKM values and are mainly known for their induction under heat stress. The chaperones encoded by dnaK and dnaJ are involved in the degradation of misfolded proteins in E. coli (26) and other bacteria after application of higher temperatures (27)(28)(29)(30). Together with hrcA and grpE, the operon structure hrcA-grpE-dnaK-dnaJ is already described in B. subtilis (31), Enterococcus faecalis (32), Streptococcus mutans (33), and others.…”
Section: Discussionmentioning
confidence: 99%